2020
DOI: 10.1136/postgradmedj-2020-137540
|View full text |Cite
|
Sign up to set email alerts
|

Novel electrocardiography parameter for paroxysmal atrial fibrillation in acute ischaemic stroke patients: P wave peak time

Abstract: IntroductionIn this study, we aimed to investigate the usefulness of P wave peak time (PWPT), a novel ECG parameter, in patients who were diagnosed with acute ischaemic stroke (IS) and had paroxysmal atrial fibrillation (PAF) on Holter monitoring.Materials and methodsIn this retrospective cohort study, we included 90 consecutive patients with acute IS who were admitted to our hospital between January 2017 and July 2019. PWPT was described as the time from the beginning of the P wave to its peak, and it was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…P‐wave‐related parameters provide clinicians with very useful information about AF 16,17 . Among these parameters, PWPT has gained an important place in predicting AF, especially in recent years 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…P‐wave‐related parameters provide clinicians with very useful information about AF 16,17 . Among these parameters, PWPT has gained an important place in predicting AF, especially in recent years 18,19 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, there has been a significant increase in diagnostics for previously undetected AF after stroke, such as long-term ECG monitoring with mobile ambulatory cardiac telemetry or implantable devices. There are also reports that have shown that a new ECG parameter, P-wave peak time, may be useful in predicting the risk of developing paroxysmal AF among patients with acute ischemic stroke [ 29 , 30 ]. Early implementation of effective cardiovascular incident prevention strategies may improve long-term survival after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, the consequent increased left atrium pressure and/or volume loading appears in the prolongation of atrial depolarization time [ 25 ]. Investigations [ 22 , 26 ] indicated the usefulness of P wave peak time and PWD to predict the ischemic events and severity of CAD. In accordance with previous studies, a predictive role of prolonged PWD for the high SYNTAX score was found in our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…During the retrospective cohort study, a total number of 876 patients were diagnosed with unstable angina. After applying the exclusion criteria, 600 patients were divided into tertiles based on the SYNTAX scores as low (0-22), intermediate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and high (≥ 33). The association between ECG parameters and SYNTAX score was investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation